Optimal growth policy: The role of skill heterogeneity - Volker Grossmann; Thomas M. Steger (Universität Leipzig, Wirtschaftswissenschaftliche Fakultät, 2012)
A simple semi-endogenous growth model is employed to show that optimal subsidization of both R&D and capital costs is independent of the distribution of R&D skills in the workforce. This holds despite the empirically supported fact that a higher R&D subsidy rate raises wages of R&D workers.
Keywords: O30; O40; H20; 330; Optimal growth policy; R&D skills; R&D subsidy; Semi-endogenous growth; Heterogeneity